A study of brainspotting therapy in PTSD using 18FDG brain PET scan to evaluate glucose metabolism changes - Foo, Mariana; Yudistiro, Ryan (Universitas Negeri Padang, 2022)
Post Traumatic Stress Disorder (PTSD) is a psychiatric and neurological disorder characterized by repeating experiences, avoidance, and hyperarousal. Brainspotting therapy (BSP) is a new body and brain treatment that claims to be effective in treating trauma and providing access to the brain. However, limited trials using neuroimaging have been done. A single-subject pretest-posttest design was applied in this study with two subjects (n = 1 PTSD; n = 1 Healthy Control; HC). Thirty sessions with online BSP were given to the PTSD subjects. 18FDG PET measurements and clinical assessment using HAM-A, DASS, and PCL-5 were taken for both subjects before and after treatment. The SDMAC value of brain 18FDG PET derived from NeuroQTMsoftware was used quantitatively between the PTSD and HC subjects to evaluate the glucose metabolism level of the mid-frontal cortex (MFC) and medial temporal cortex(MTC), which is associated with PTSD. Measurements taken post-treatment for clinical assessment exhibited a reduction in PTSD symptoms while PET scans demonstrated varied results. The findings of this study indicate that online BSP is effective for improving PTSD symptoms and has various effects on brain glucose metabolism. The limitations and suggestions of the study are discussed for further research.